Analisis Overall Equipment Effectiveness dalam Penerapan Total Productive Maintenance Pada Mesin Flow Mixer di PT ASI - Wilarso; Bayu Hamengku Rizkiansyah; Asep Dharmanto; Asep Saepudin; Mujiarto (Universitas Wahid Hasyim, 2026)
Improving machine productivity and effectiveness is a crucial factor in maintaining the competitiveness of manufacturing companies. One approach to improving equipment performance is Total Productive Maintenance (TPM), with Overall Equipment Effectiveness (OEE) as the primary indicator. This study aims to analyze the effectiveness of the Flow Mixer machine at PT ASI's Mold Shop Department based on its OEE value, which comprises availability, performance, and quality. It also identifies the dominant factors causing low machine effectiveness using the Six Big Losses approach and a fishbone diagram. The research data were obtained from production data, planned and unplanned downtime, the number of defective products, and machine operating time during September–November 2025. The calculation results show that the Flow Mixer machine's OEE values ​​were 66% (September), 68% (October), and 68% (November), respectively, which are still below the world-class OEE standard of 85%. The main factors influencing the low OEE are breakdowns and process defect loss. Improvement proposals are based on the eight pillars of TPM, which focus on improving machine maintenance, operator skills, and standardizing work procedures. Implementation of the proposed improvements in December resulted in an increase in the OEE value to 72%. The results of this study demonstrate that consistent TPM implementation can improve the effectiveness of the Flow Mixer machine and the productivity of the production process.